2016
DOI: 10.1038/srep38579
|View full text |Cite
|
Sign up to set email alerts
|

An ERβ agonist induces browning of subcutaneous abdominal fat pad in obese female mice

Abstract: Estrogen, via estrogen receptor alpha (ERα), exerts several beneficial effects on metabolism and energy homeostasis by controlling size, enzymatic activity and hormonal content of adipose tissue. The actions of estrogen on sympathetic ganglia, which are key players in the browning process, are less well known. In the present study we show that ERβ influences browning of subcutaneous adipose tissue (SAT) via its actions both on sympathetic ganglia and on the SAT itself. A 3-day-treatment with a selective ERβ ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 38 publications
4
31
0
Order By: Relevance
“…21,48 LY 3201 is one of the specific agonists of ERβ that has been proved to effectively and characteristically activate ERβ but not α that renders it of great clinical application value. 16 Consistent with the in vivo findings, our in vitro results showed that activation of ERβ 21,49 Thus, on the one hand, ERβ absence leads to more adipocyte differentiation during early healing process which interrupts ideal repair. On the other hand, whether increased adipocyte differentiation inhibits tenocyte differentiation needs further investigation.…”
Section: Discussionsupporting
confidence: 88%
“…21,48 LY 3201 is one of the specific agonists of ERβ that has been proved to effectively and characteristically activate ERβ but not α that renders it of great clinical application value. 16 Consistent with the in vivo findings, our in vitro results showed that activation of ERβ 21,49 Thus, on the one hand, ERβ absence leads to more adipocyte differentiation during early healing process which interrupts ideal repair. On the other hand, whether increased adipocyte differentiation inhibits tenocyte differentiation needs further investigation.…”
Section: Discussionsupporting
confidence: 88%
“…In a recent series of preclinical studies, [151][152][153] it was demonstrated that ERβ-specific ligands have powerful antiobesity effects and increase energy expenditure and mitochondrial activity in adipose tissues, including in the setting of ovarian hormone deficiency. In a recent series of preclinical studies, [151][152][153] it was demonstrated that ERβ-specific ligands have powerful antiobesity effects and increase energy expenditure and mitochondrial activity in adipose tissues, including in the setting of ovarian hormone deficiency.…”
Section: Estrogen Receptor Betamentioning
confidence: 99%
“…While the mechanisms by which signaling through ERβ may have antiobesity effects are not clear, new evidence implicates ERβ as a primary mediator of 17β-E2's protective metabolic effects regarding adipose tissue mitochondrial activity. In a recent series of preclinical studies, [151][152][153] it was demonstrated that ERβ-specific ligands have powerful antiobesity effects and increase energy expenditure and mitochondrial activity in adipose tissues, including in the setting of ovarian hormone deficiency. 150 A major caveat is that the majority of these studies investigating isotype-specific effects of ER signaling have been done in rodent models, not humans.…”
Section: Estrogen Receptor Betamentioning
confidence: 99%
“…It has been demonstrated that estrogens are involved in the regulation of metabolic processes by investigating the actions of ERα and ERβ using appropriate models lacking either ERα (αERKO) [10] or ERβ (βERKO) [11,12]. Aromatase knockout (ArKO) [13] or ovariectomized (OVX) [14] mice are also models that are frequently used in research on estrogen receptor signaling due to loss of, or reduced, circulating estrogens.…”
Section: Erα Versus Erβ Laboratory Mouse and Ligands In Metabolic Stmentioning
confidence: 99%
“…Moreover, the activation of ERs by synthetic ligands/agonists is another approach used in endocrinology studies in both males and females that may better reflect human physiology. A large number of ERβ-selective ligands including DPN [11], WAY200070 [15], β-LGNDs [8,12], LY3201 [10] and DIP [6,9] have been used to further investigate the role of ERβ in metabolic homeostasis.…”
Section: Erα Versus Erβ Laboratory Mouse and Ligands In Metabolic Stmentioning
confidence: 99%